INVESTASI TIONGKOK PASCA DEGRADASI IKLIM INVESTASI 1MDB - Auliya, Harisah ‘Aini; Tjarsono, Idjang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Chinese President Xi Jinping and Malaysian Prime Minister,Najib Razak, in 2013 agreed to improve bilateral strategic partnership relationships. China invests in infrastructure, property, industry and economic sectors along the One Belt One Road sea route in an effort to protect supplies and have political influence through the Strait of Malacca. China is also helping to restore the debt of troubled state assets 1Malaysia Development Berhad with a large amount of investment. This study aimed to explain the steps taken by China which is very surprising considering that Malaysia has a complex problem about the investment state assets of 1MDB. This research guided by a qualitative explanation method and the data obtained comes from books, journals, report, working papers, internet sites and other sources related to research. The focus of this research is why China keep on investing a huge amount in Malaysia that was in degradation of investment climate after nation-asset 1MDB trouble. The theoretical framework applied in this research are neo-liberalism supported by the theory of interdependence by Keohane and Nye, theory of determinants of foreign direct investment by Dunning and China Outward Direct Investment by Buckley to strengthen the goals and opportunities that exist in Malaysia that make China confident to provide large-scale investment. The research showed that China investments in Malaysia has attracted by opportunity in Malaysia’s potential economic market. China is Malaysia's largest trading partner and Malaysia is top 3 China's largest trading partner in Southeast Asia and the history relations between countries. Even after the investment degradation, China still managed developing investments in infrastructure through Pan Asia Railway Network, expanding property by Bandar Malaysia projects, developing energy resources by buying a whole stocks of Edra Global Energy Bhd and building any sectors that could facilitate the One Belt One Road agenda. Keywords : Chinese Investment, 1Malaysia Development Berhad, One Belt One Road,